1986
DOI: 10.1002/iroh.19860710405
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Stream Ecosystems: Variability in Environmental Properties and Algal Community Structure

Abstract: The variability in physical, chemicaland biologicalpropertieswas examinedforanumberof glacier melt streams in south Victoria Land, Antarctica. Streams flowed for between one and two months. Stream water temperatures (range =0-11 "C) varied over short (hr) time scales whilst discharges varied considerably between streams (range 0.001-15 mJ s-1) and over die1 cycles. Solar radiation and air temperature were major determinants of stream discharge. Variability in discharge was reflected in variability in nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…UZothrix sp. have either been found in the icefree valleys of southern Victoria Land (Broady, 1982b;Howard-Williams et al, 1986) or at Edmondson Point, northern Victoria Land (Broady, 1987). In those regions, rich growths of green filaments and ribbons comprise Binuclearia tectorum, Prasiola calophyllu and Tribonema elegans.…”
Section: Algae In Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…UZothrix sp. have either been found in the icefree valleys of southern Victoria Land (Broady, 1982b;Howard-Williams et al, 1986) or at Edmondson Point, northern Victoria Land (Broady, 1987). In those regions, rich growths of green filaments and ribbons comprise Binuclearia tectorum, Prasiola calophyllu and Tribonema elegans.…”
Section: Algae In Streamsmentioning
confidence: 99%
“…Goldman et al (1972) made brief observations on pond and lake algae and HohnHansen (1964) cultured algae from ponds and soils. The nutrient physiology of algae in ponds at 78 C. Bird and C. Royds was studied by Vincent & Vincent (1982), and Howard-Williams et al (1986) examined the characteristics of a stream at C. Bird. Observations on algae in four ponds at C. Bird were provided by Zaneweld (1969) and in a single pond by Spurr (1975).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, these ecosystems comprise a substantial proportion of the total number, length, and discharge of fluvial networks (Larned et al 2010). For instance, more than half of the total river length in South Africa (Uys and O'Keefe 1997), USA (Nadeau and Rains 2007), and Greece (Tzoraki et al 2007) is subject to flow intermittency, and in the Arctic and Antarctic regions virtually all running waters are temporary (Howard-Williams et al 1986). In the Mediterranean basin, temporary streams are the dominant surface water type (Gasith and Resh 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The recalculated values of the gross primary production rates from our laboratory data are two or three orders of magnitude lower than previously measured field data. The gross periphyton primary production rate in polar streams (measured either as ash-free DW, oxygen production, or as 14 C uptake) was in the range 0.39Á4.53 mg C cm (2003) and Howard-Williams & Vincent (1989) also showed that benthic stream communities in Antarctica, either in the ponds of the McMurdo Ice Shelf or in the snow-melt streams on King George Island, were extremely rich in non-chlorophyll organic carbon. Even if it is considered that the phytoplankton primary production in polar lakes, expressed as the photosynthesis rate, is generally low compared to other cold waters (below 0.16Á1.12 g C g (1 Chl a h (1 ; Markager et al 1999).…”
Section: Comparison Of In Situ and In Vivo Measurementsmentioning
confidence: 86%
“…However, their nutrient content, and therefore water trophic status, could be increased from external nutrient sources like rookeries or by increased weathering of rocks (Vincent & LaybournParry 2008). The microalgae and cyanobacteria of these streams represent one of the most important parts of polar freshwater ecosystems (Elster 2002;Elster & Benson 2004), because the amount of fixed carbon is not only significant for the polar regions, but for the whole planet as well (e.g., Howard-Williams et al 1986;Vincent 1988;Vincent et al 1993;Vincent & James 1996;Elster 2002). Microalgal and cyanobacterial primary production rates are sensitive to changes in physical, chemical and biological environmental factors.…”
Section: Introductionmentioning
confidence: 99%